From Bulk to Nanoparticles: An Overview of Antiviral Materials, Its Mechanisms, and Applications. (26th June 2021) - Rodrigues, Isabella C. P.; Campo, Kaio N.; Arns, Clarice W.; Gabriel, Laís P.; Webster, Thomas J.; Lopes, Éder S. N.
Abstract: Infectious diseases caused by viruses are a global health concern and have become prominent in light of the recent COVID‐19 pandemic. Considering the limitations of drugs and prophylactic methods used in current medicine, antiviral materials are a useful strategy in preventing the spread of viruses and enhancing treatment efficiency. Thus, this review highlights the state‐of‐the‐art antiviral materials, describes the scientific landscape of the primary antiviral materials used based on bibliometric analysis, presents their mechanisms of action, and discusses their clinical applications. The mechanisms of action underlying the broad‐spectrum antiviral properties of metals, ceramics, polymers, and composites are also discussed. Polyanions, polycations, oxides, and metal‐based materials, from bulk to nanoparticles, have good potential in antiviral applications that may help prepare the world for future viral breakouts. Abstract : Recent progress in materials designed against viruses is reviewed here with respect to the main antiviral mechanisms and applications of metals, polymers, ceramics, and composites. Antiviral materials discussed in the literature from bulk to nanoparticles are presented, guided by bibliometric analysis. Metal‐based surfaces and nanoparticles, oxides, carbon nanostructures, polycations, and polyanions are some promising materials explored with a broad‐spectrum of antiviral activity.